THE MIRROR BREAK: SEXUALITY AND IDENTITY IN HAMLET - Pimenta, Leny Andre [UNESP]; Momesso, Maria Regina [UNESP]; Marcal Ribeiro, Paulo Rennes [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2017)
This article it proposes to reflect on issues of sexuality and identity in Hamlet. The analysis corpus is a cutout of three scenes of digital RPG Mabinogi: Hamlet - 'To be, or not to be'. The digital format is made up of a hybrid languages and this causes a (re) configuration educational therefore triggers the digital player and player different abilities and skills of print media. It is known that sexuality has been problematized, throughout history, through literature and reflections who subscribe to different cultural languages, from the various practices and discourses circulating in that produce subjectivity possibilities. Given the above it is intended to meet the concerns that generate some questions: Literature, enrolled in a digital format, favors the experience of self in relation to the daily life of human sexuality? The desire of hatred is what drives the mirror breaks for recognizing you? The theoretical-methodological apparatus of this reflection is based on French discursive perspective and bias of Lacanian psychoanalysis. It is observed that the subject can, through literature, be taken to observe yourself, be analyzed if decipher, recognizing as a domain of its truth, and accordingly its subjectivity builds your understanding of what is sexuality or highlights the repression of misunderstood desires.
Keywords: Sexuality; Identity; Speech; Psychoanalysis